100 Somatic Mosaicism of a PDGFRB Activating Variants in Intracranial, Coronary, Aortic and Radial Vascular Beds. (1st April 2022) - McAvoy, Malia; Parada, Carolina; El-Ghazali, Fatima; Toglia, Daphne; Ruzevick, Jacob; Emerson, Samuel; Karasozen, Yigit; Busald, Tina; Nazem, Ahmad; Suranowitz, Shaun; Shalhub, Sherene; Marshall, Desiree; et al.
Abstract : INTRODUCTION: Activating variants in platelet-derived growth factor receptor beta (PDGFRB) are associated with aneurysms. Our group previously described a patient with multiple fusiform intracranial aneurysms who was found to have a somatic mosaic variant in PDGFRB. The relationship between the mosaic effects of PDGFRB variants and the vascular phenotypes is not well understood. METHODS: Following death due to subarachnoid hemorrhage, samples from the index patient's intracranial, coronary, aortic, and radial arteries were biopsied and preserved. DNA was extracted and alternate allele fractions (AAF) of PDGFRB variants were determined using digital droplet PCR. Histopathological analysis was performed by a board-certified neuropathologist. RESULTS: A total of 80 biopsies were obtained. The AAFs of variant PDGFRB in the vertebral artery, basilar artery, and P1 segment aneurysms were 28.7%, 16.4%, and 17.8%, respectively. The AAF of the coronary and radial artery aneurysms were 22.3% and 20.6%, respectively. AAFs of normal vascular biopsies of the intracranial circulation, coronary arteries, and aorta ranged from 0 to 4.3%, 0 to 0.3%, and 0 to 35%, respectively. The PDGFRB variant was absent from lymphocyte DNA and normal tissue, confirming it to be a non-germline somatic variant. Expression of PDGFRB within the radial artery aneurysmal tissue was localized to CD31 negative, non-endothelial cell origin. CONCLUSION: Somatic mosaic expression of PDGFRB within CD31 negative cells is associated with development of fusiform aneurysms. The role of targeted therapy with tyrosine kinase inhibitors to locally alter the biology of aneurysm development in fusiform aneurysms with PDGFRB mutations should be further studied.